Preclinical Toxicity Evaluation of Clinical Grade Placenta-Derived Decidua Stromal Cells - Sadeghi, Behnam; Moretti, Gianluca; Arnberg, Fabian; Samén, Erik; Kohein, Bita; Catar, Rusan; Kamhieh-Milz, Julian; Geissler, Sven; Moll, Guido; Holmin, Staffan; Ringdén, Olle (Frontiers in Immunology, 2019)
Placenta-derived decidua stromal cells (DSCs) are being investigated as an alternative to other sources of mesenchymal stromal cells (MSCs) for cellular therapy. DSCs are more effective in treating acute inflammatory diseases in human and this is our preclinical safety study of human DSCs in Sprague-Dawley rats and Balb/c mice. Human DSCs were cultured and expanded from fetal membranes obtained from placentas following caesarean section. In rats, 0.5 x 106 cells/kg were injected intravenously (n = 6) or intra-aortal (n = 6). In mice, DSCs were given intravenously at doses ranging from 4-40 x 106 cells/kg (total of n = 120 mice). In vivo tracking of human cells in mice was performed by using transduced DSC with luciferin gene, and in rats by using 18F-FDG PET. Clotting parameters were determined in vitro and in vivo. All intra-arterially DSC-treated rats had normal motility and behavior and histological examination was normal for liver, spleen kidneys and thigh muscles. Mice treated with DSCs showed no immediate or long-term side effects. None of the mice died or showed acute toxicity or adverse reactions 3- and 30-days after DSC infusion. Murine blood biochemistry profiles related to liver, kidney, heart and inflammatory indices was not influenced by DSC infusion and complete blood counts were normal. In vivo tracking of infused DSCs detected a signal in the lungs for up to 4 days post infusion. Compared to bone marrow derived MSCs, the DSCs had better viability, smaller size, but stronger clotting in human blood and plasma. Both MSC- and DSC-induced coagulation and complement activation markers, thrombin-anti-thrombin complex (TAT) and C3a, and in vitro clotting parameters were decreased by heparin supplementation. In conclusion, DSCs are safe with almost no side effects even with doses 40 times higher than are used clinically, particularly when supplemented with low-dose heparin.